2008
DOI: 10.2527/jas.2008-1114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body condition score at parturition and postpartum protein supplementation on estrous behavior and size of the dominant follicle in beef cows1,2

Abstract: The objective of this study was to determine the effects of BCS at calving and the amount of postpartum protein supplementation on the dominant follicle (DF) and behavioral characteristics at the first postpartum estrus of mature beef cows. Multiparous Angus x Hereford cows (n = 45) were fed to calve in thin (T; < 5) or moderate (M; >or=5) BCS. Cows were stratified by BCS and calving date, and randomly assigned to receive lesser (L; 1.2 kg/d) or greater (G; 2.5 kg/d) amounts of a 42% CP supplement. All cows gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 51 publications
4
33
1
7
Order By: Relevance
“…More studies are required to critically evaluate the role of these parameters prepartum. Recently, Lents et al [6] as expected, found that pregnancy rate of cows with moderate condition during the breeding season is greater than cows with thin condition at calving. How this observation relates to events late in pregnancy remains to be tested.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…More studies are required to critically evaluate the role of these parameters prepartum. Recently, Lents et al [6] as expected, found that pregnancy rate of cows with moderate condition during the breeding season is greater than cows with thin condition at calving. How this observation relates to events late in pregnancy remains to be tested.…”
Section: Discussionmentioning
confidence: 73%
“…Previous work to establish optimum body weight or condition score at calving for a prompt resumption of ovarian activity has rendered conflicting results. Lents et al [6] suggested that cows should be managed to calve during moderate BCS and to maintain body weight (BW) after parturition to decrease the interval to first estrus. However, prior work [7] had indicated that when beef cows are in thin to moderate body condition at calving, postpartum BW change and BCS at calving do not influence the duration of luteal activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature supports that cows in moderate BCS (5-6) have increased conception rates (Lents et al 2008;Bohnert et al 2013) and decreased postpartum interval (Lents et al 2008) when compared with cows that are in poor BCS (4). In Exp.…”
Section: Methodsmentioning
confidence: 90%
“…Embryo transfer became a viable option for the North American beef industry during the early 1970s (Hasler 2003). Considerable evidence exists which implicates that prepartum nutritional management will improve subsequent reproductive performance in beef cattle (Sasser et al 1988;Selk et al 1988;Lents et al 2008). Prepartum nutrition affects BW and BCS (Stalker et al 2006;Bohnert et al 2013) and can alter circulating hormone concentrations (Wiley et al 1991;Lalman et al 1997) that are important in cattle achieving reproductive success.…”
Section: Introductionmentioning
confidence: 99%
“…Vücut kondisyon skoru ile preovulatör follikül çapı arasında bir ilişki gözlenme-miştir. Ancak yapılan bazı çalışmalarda preovulatör follikül çapının, sunulan çalışmada kullanılan ineklerde olduğu gibi spontane değilde, follikül gelişimi ve ovulasyonun eksternal hormonlarla indüklenmesi durumunda önemli etkiye sahip olduğu yönündedir (5,15).…”
Section: Tartışma Ve Sonuçunclassified